2020
DOI: 10.1101/2020.02.03.20019760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating tumor DNA in neoadjuvant treated breast cancer reflects response and survival

Abstract: Pathologic complete response (pCR) to neoadjuvant chemotherapy (NAC) is strongly associated with favorable outcome. We examined the utility of serial circulating tumor DNA (ctDNA) testing for predicting pCR and risk of metastatic recurrence in 84 high-risk early breast cancer patients treated in the neoadjuvant I-SPY 2 TRIAL. Cell-free DNA (cfDNA) was isolated from 291 plasma samples collected at pretreatment (T0), 3 weeks after initiation of paclitaxel (T1), between paclitaxel and anthracycline regimens (T2),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 44 publications
5
37
0
5
Order By: Relevance
“…Patients with malignant melanoma, who may have a higher response rate to pembrolizumab than the other patients enrolled in INSPIRE, displayed the lowest average ctDNA levels. Of note, patients with TNBC were among those with the highest baseline ctDNA levels, which is consistent with other findings that ctDNA levels are higher in TNBC than other breast cancer subtypes 24 . Baseline ctDNA levels were not strongly correlated with RECIST target lesion measurements (which does not incorporate measurements from nontarget lesions), suggesting that ctDNA could provide complementary information to RECIST.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with malignant melanoma, who may have a higher response rate to pembrolizumab than the other patients enrolled in INSPIRE, displayed the lowest average ctDNA levels. Of note, patients with TNBC were among those with the highest baseline ctDNA levels, which is consistent with other findings that ctDNA levels are higher in TNBC than other breast cancer subtypes 24 . Baseline ctDNA levels were not strongly correlated with RECIST target lesion measurements (which does not incorporate measurements from nontarget lesions), suggesting that ctDNA could provide complementary information to RECIST.…”
Section: Discussionsupporting
confidence: 91%
“…Li et al studied plasma samples before, during and after neoadjuvant chemotherapy in 52 patients and demonstrated that ctDNA analysis after 2 cycles of treatment correlated better with pCR probability than radiological diagnostic work-up 34 . Similar results were reported by Magbanua et al, who performed ctDNA ultra-deep sequencing in 84 patients treated in the I-SPY 2 trial 35 . Within 3 weeks after treatment was started, the ctDNA positivity rate dropped sharply from 73 to 35%.…”
Section: Clinical Applications Of Liquid Biopsy In Early Breast Cancesupporting
confidence: 87%
“…Li et al untersuchten Plasmaproben vor, während und nach der neoadjuvanten Chemotherapie bei 52 Patientinnen und konnten zeigen, dass die Bestimmung der ctDNA nach 2 Zyklen der Therapie mit der pCR-Wahrscheinlichkeit besser korreliert als die radiologische Diagnostik 34 . Ähnliche Ergebnisse wurden von Magbanua et al berichtet, die ctDNA mittels Ultra-deep Sequencing bei 84 im Rahmen der I-SPY 2-Studie behandelten Patientinnen untersuchten 35 . Bereits 3 Wochen nach Beginn der Therapie zeigte sich ein starker Abfall der ctDNA-Positivitätsrate von 73 auf 35%.…”
Section: Therapiemonitoring Mittels Liquid Biopsyunclassified
“…Furthermore, a decrease in ctDNA levels was detected during neo-adjuvant therapy [140]. This strategy was also adopted in another recent study with the specific aim of utilizing the ctDNA assay for predicting complete pathological response in 84 high-risk early BC patients treated with the neoadjuvant I-SPY2 TRIAL [141]. The results of this interesting study revealed that lack of ctDNA clearance was a significant predictor of poor response and metastatic recurrence, while clearance was associated with improved survival independent of the pathological response [141].…”
Section: Breast Cancermentioning
confidence: 99%
“…This strategy was also adopted in another recent study with the specific aim of utilizing the ctDNA assay for predicting complete pathological response in 84 high-risk early BC patients treated with the neoadjuvant I-SPY2 TRIAL [141]. The results of this interesting study revealed that lack of ctDNA clearance was a significant predictor of poor response and metastatic recurrence, while clearance was associated with improved survival independent of the pathological response [141]. These studies support the view that personalized monitoring of ctDNA during neo-adjuvant chemotherapy may assist in real-time assessment of treatment response, and together with pathological response, may contribute to predicting the patient's survival.…”
Section: Breast Cancermentioning
confidence: 99%